An Ethnobotany Research Training Workshop in Madagascar - McClatchey, Will; Gollin, Lisa X. (Ethnobotany Research and Applications, 2005)
A consortium of conservation groups organized by the Missouri Botanical Garden in 2005 responded to a call for development of conservation areas in Madgascar that would include human communities within them by arranging for a training workshop on ethnobotanical research methods. The authors developed and implemented the workshop with sixteen participating Malagasy researchers. The content of the workshop and analyses of classroom and field components is provided. The workshop participants concluded that the process was very useful for their work in conservation of biological diversity and determined to continue to develop their skills in ethnobotanical research as a group of collaborating scholars.